Synthesis and in vitro evaluation of novel lipophilic monophosphorylated gemcitabine derivatives and their nanoparticles - Lansakara-P, Dharmika S. P. (2012)
Gemcitabine hydrochloride (HCl) is approved for the treatment of a wide spectrum of solid tumors. However, the rapid development of resistance often makes gemcitabine less efficacious. In the present study, we synthesized several novel lipophilic monophosphorylated gemcitabine derivatives, incorporated them into solid lipid nanoparticles, and then evaluated their ability to overcome major known gemcitabine resistance mechanisms by evaluating their in vitro cytotoxicities in cancer cells that are deficient in deoxycytidine kinase (dCK), deficient in human equilibrative nucleoside transporter (hENT1), over-expressing ribonucleotide reductase M1 subunit (RRM1), or over-expressing RRM2. In dCK deficient cells, the monophosphorylated gemcitabine derivatives and their nanoparticles were up to 86-fold more cytotoxic than gemcitabine HCl. The majority of the gemcitabine derivatives and their nanoparticles were more cytotoxic than gemcitabine HCl in cells that over-expressing RRM1 or RRM2, and the gemcitabine derivatives in nanoparticles were also resistant to deamination by deoxycytidine deaminase. The gemcitabine derivatives (in nanoparticles) hold a great potential in overcoming gemcitabine resistance.